Implementasi Evaluasi Hasil Belajar Pendidikan Agama Islam di Madrasah - Warsah, Idi; Habibullah, Habibullah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this study was to determine the implementation of the evaluation of Islamic religious education learning outcomes implemented by madrasas and whether the measuring tools used in measuring learning outcomes of Islamic religious education in Madrasas were valid and reliable, that is, they were able to measure according to what they wanted to measure and the results obtained could be measured. trusted. The method used in this research is Library Research. The results of the study, the implementation of learning evaluation in this case is one of the assessment systems. Assessment is an important part in the management of education to obtain information on the development of students and the achievement of predetermined graduate competency standards. The assessment is carried out by educators and educational units using reference criteria, which are based on the principles: valid, objective, fair, integrated, open, comprehensive and sustainable, systematic, based on criteria and accountable. Conclusion, In conclusion, the implementation of evaluation in Madrasahs is carried out in the form of continuous assessments aimed at monitoring the learning process and progress of students and to improve learning effectiveness. Effective learning management supported by a good assessment of learning outcomes will have a positive effect on improving the quality of education in madrasas. Keywords: Education Evaluation, Islamic Religion, Madrasah